S.O.S. Mathematics CyberBoard

Your Resource for mathematics help on the web!
It is currently Fri, 9 Dec 2016 06:42:54 UTC

All times are UTC [ DST ]

Post new topic Reply to topic  [ 1 post ] 
Author Message
PostPosted: Mon, 29 Mar 2010 19:51:00 UTC 
User avatar

Joined: Wed, 30 Mar 2005 04:25:14 UTC
Posts: 15563
Location: Austin, TX
I was looking at Exam A from the Putnam from last December and one of the problems looked like a fun thing to spend a couple of minutes trying. It's not hard by any stretch of the imagination, but the method was rather novel, and I think it will be fun for those with even the most rudimentary understanding of DiffEQ.

Functions f,\, g, and h are differentiable on some open interval around 0 and satisfy the equations and initial conditions

f'=2f^2gh+{1\over gh}\quad f(0)=1 \\
g'=fg^2h+{4\over fh}\quad g(0)=1  \\
h'=3fgh^2 + {1\over fg}\quad h(0)=1

Find an explicit formula for f(x) valid on some open interval around 0.

Hint 1:

Product rule

Hint 2:
semi-clever replacement

My solution:

Start by noting that the identically zero function for any of the three is invalid by the division part of the equations, so multiplying all of the equations by f,\, g, or his a valid operation.

Then we have:

f'gh=2(fgh)^2+1\quad f(0)=1 \\
fg'h=(fgh)^2+4\quad g(0)=1  \\
fgh'=3(fgh)^2 + 1\quad h(0)=1

Add these together and note that we are in a situation where we have applied the product rule to the function m:=fgh, so we get:


The semi-clever replacement is to note that Dm=D(m-1)

So solving the differential equation:

D(m-1)-6(m-1)=0 is simple, it gives that

m=Ae^{6x}-1 by use of the characteristic equation method.

Now the initial condition m(0)=1 tells us that A=2.

Now returning to the equation

${df\over dx}=f\left(2m+{1\over m}\right)\quad f(0)=1

we can see by simple separation of variables that

$\log f=2\int (2e^{6x}-1)\,dx +\int{dx\over 2e^{6x} -1}

which yields

$\log f = \left({2\over 3}e^{6x}-2x\right)+\left({1\over 6}\log{\left| 1-2e^{6x}\right|}-x\right)+C

The second integral coming from adding and subtracting 1 and making a u-substitution.

Using our initial conditions, we find that 0={2\over 3}+C\Rightarrow C=-{2\over 3}

From there it's a simple exponentiation to recover f completely.

(\ /)
(> <)
This is Bunny. Copy Bunny into your signature to help him on his way to world domination

Display posts from previous:  Sort by  
Post new topic Reply to topic  [ 1 post ] 

All times are UTC [ DST ]

Who is online

Users browsing this forum: No registered users

You cannot post new topics in this forum
You cannot reply to topics in this forum
You cannot edit your posts in this forum
You cannot delete your posts in this forum

Search for:
Jump to:  
Contact Us | S.O.S. Mathematics Homepage
Privacy Statement | Search the "old" CyberBoard

users online during the last hour
Powered by phpBB © 2001, 2005-2016 phpBB Group.
Copyright © 1999-2016 MathMedics, LLC. All rights reserved.
Math Medics, LLC. - P.O. Box 12395 - El Paso TX 79913 - USA